2018
DOI: 10.1007/s12020-018-1679-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of E and N-cadherin in the postoperative course of gonadotroph pituitary tumours

Abstract: We found that silent gonadotroph tumours presented high IRS for N-cadherin and low IRS for the extracellular domain of E-cadherin. A substantial proportion of the tumours presented nuclear staining for the intracellular domain of E-cadherin, accompanied by a reduced membranous expression of the intracellular domain of E-cadherin. Absence of nuclear staining for the intracellular domain of E-cadherin served as an independent predictor of reintervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 43 publications
4
30
0
Order By: Relevance
“…The ECM plays a critical role in tumorigenesis and invasiveness/aggressiveness in several cancers, being a bridge between cell differentiation and proliferation, angiogenesis, and cell motility. The epithelial–mesenchymal transition process (EMT) has previously been studied in several subtypes of pituitary tumors and found to be of importance for both hormone production and aggressiveness [ 38 , 39 , 40 , 41 ]. Interestingly, in a recent multi-omics study, the silent corticotroph tumors presented low EMT, whereas USP8-wild-type functioning tumors showed and increased EMT, somehow challenging the classical imagistic phenotype of SCA as an aggressive tumor [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ECM plays a critical role in tumorigenesis and invasiveness/aggressiveness in several cancers, being a bridge between cell differentiation and proliferation, angiogenesis, and cell motility. The epithelial–mesenchymal transition process (EMT) has previously been studied in several subtypes of pituitary tumors and found to be of importance for both hormone production and aggressiveness [ 38 , 39 , 40 , 41 ]. Interestingly, in a recent multi-omics study, the silent corticotroph tumors presented low EMT, whereas USP8-wild-type functioning tumors showed and increased EMT, somehow challenging the classical imagistic phenotype of SCA as an aggressive tumor [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oestrogen induces expression of pituitary tumour transforming gene (PTTG) 50 and modulates epithelial-cadherin (E-cadherin). 51 In a cohort study of NFPT, increased ERα together with decreased E-cadherin and ERβ expression were observed in invasive compared with non-invasive tumours. 52 By contrast, other studies have linked loss of ERα expression with propensity for resistance to conventional therapies and early re-intervention in lactotroph and NFPT.…”
Section: Oestrogen Receptor α (Erα)mentioning
confidence: 97%
“…71,72 During EMT, membranous E-cadherin is translocated to the nucleus. 51 Several studies have demonstrated…”
Section: Epithelial-mesenchymal Transition (Emt) and Extracellular Matrix (Ecm) Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…The cadherin family, a class of Ca 2+ -dependent transmembrane glycoproteins, serves an important role in tissue morphogenesis and coordination of cell movement(42). E-cadherin and N-cadherin are two representatives of the cadherin family and are associated with EMT(43,44). Thus, increases in MMP2, MMP9, N-cadherin…”
mentioning
confidence: 99%